Natural Plant Extracts and Microbial Antagonists to Control Fungal Pathogens and Improve the Productivity of Zucchini (Cucurbita pepo L.) In Vitro and in Greenhouse - Hanaa S. Hassan (MDPI AG, 2021)
Background: Natural plant extracts and microbial antagonists have the potential for use in increasing the fungal resistance and productivity of horticulture plants. Methods: The purpose of this study was to evaluate the ability of both natural plant extracts and microbial antagonists as a biotical control of some fungal pathogens, i.e., Fusarium ssp., Exserohilum ssp. and Nigrospora ssp., along with improving the growth and productivity performance of zucchini under greenhouse conditions. Eucalyptus camaldulensis leaf extract (LE), Citrus sinensis LE, Ficus benghalensis fruit extract (FE), and two microbial antagonists Pseudomonas fluorescens (accession no. MW647093) and Trichoderma viride (accession no. MW647090) were tested under in vitro and in vivo conditions. Through morphological characteristics and the internal transcribed spacer (ITS) region, Fusarium solani (accession no. MW947256), F. oxysporum (accession no. MW947254), Exserohilum rostratum (accession no. MW947255), and Nigrospora lacticolonia (accession no. MW947253) were identified. HPLC analysis was used for the identification of phenolic compounds (PCs) and flavonoid compounds (FCs) in the extracts. Results: The highest inhibition percentage of fungal growth (IPFG) against F. oxysporum was obtained with P. fluorescens, T. viride, and E. camaldulensis LE (4000 mg/L); F. solani with P. fluorescens, T. viride, and C. sinensis LE (4000 mg/L); Exserohilum rostratum with P. fluorescens, Ficus benghalensis FE (4000 mg/L) and E. camaldulensis LE (4000 mg/L), and N. lacticolonia with P. fluorescens. Using HPLC analysis, the abundant PCs in E. camaldulensis LE were pyrogallol, and caffeic acid, those in C. sinensis LE were syringic acid and ferulic acid, and those in F. benghalensis FE were gallic acid and syringic acid. In addition, the abundant FCs in E. camaldulensis LE were kaempferol, and naringin, those in C. sinensis LE were hesperidin and quercetin, and those in F. benghalensis FE were kaempferol and quercetin. Under greenhouse experiments, T. viride and E. camaldulensis LE (4000 mg/L) followed by P. fluorescens + T. viride treatments gave the best results of zucchini plants in terms of leaf area, fruits number per plant, yield per plant, and total yield (marketable and non-marketable). Conclusions: Plant extracts and bioagents can be used to control some zucchini fungal pathogens and increase the productivity performance of zucchini plants.